Survival Prediction for Clear Cell Renal Cell Carcinoma Based on Deep Multimodal Synergistic Survival Network - Liang Liang; Jianing Xu; Yu Zhang (Physics in Medicine & Biology, 2026)
Abstract Objective. To propose a deep multimodal synergistic survival analysis framework (Deep Multimodal Synergistic Survival Network, DMSSN) to achieve accurate prognostic analysis for clear cell renal cell carcinoma (ccRCC). Methods. This study (DMSSN) utilized matched multimodal data from the TCGA-KIRC database, including CT imaging data, whole slide images (WSI), copy number variation (CNV) features, and clinical data. Deep Canonical Correlation Analysis (DCCA) was employed to map heterogeneous modalities into a shared latent space. Contrastive learning was introduced to enhance semantic consistency across multimodal features, and a gating network was utilized for the adaptive fusion of multimodal information to achieve precise survival risk prediction for patients. Results. Experimental results demonstrated that DMSSN achieved a Concordance Index (C-index) of 0.8153 ± 0.0994, with a Log-rank test p-value of 1.6553E-11. DMSSN exhibited significant performance advantages over traditional statistical methods like Log-rank-Cox (0.7055 ± 0.0670) and machine learning methods such as Random Survival Forest (RSF) (0.6836 ± 0.1048). Furthermore, in comparison with similar deep learning approaches, DMSSN outperformed late fusion strategies (0.7493 ± 0.1211) and discrete-time survival models such as DeepHit (0.7655 ± 0.1041) and Nnet-surv (0.7694 ± 0.0635). Notably, DMSSN still achieved the best predictive performance when compared to the classic deep survival model DeepSurv (0.7919 ± 0.0978) and advanced state-of-the-art multimodal fusion frameworks like CHIEF (0.7735 ± 0.0818) and MCAT (0.8102 ± 0.0972). Ablation studies showed that removing any single modality led to a decline in performance, with the most significant drop occurring after removing CT imaging features (C-index decreased to 0.7327), validating the complementarity of multimodal data and the pivotal role of radiomic features in prognostic assessment. Module ablation experiments further confirmed the effectiveness of the core components. Conclusion. By effectively integrating imaging, pathology, genomic, and clinical features, the DMSSN framework demonstrates superior performance and robustness in the survival prediction of ccRCC.